Translation and Cross-Language Validation of the Brief Self-Esteem Inventory in Urdu Language - Dr. Anila Sadaf Mubashir; Rida Kainaat; Samia Azeem; Maha Mustafa (Social Science Review Archives, 2025)
The present study aimed to translate the Brief Self-Esteem Inventory (BSEI) into Urdu language and to validate its psychometric properties within the Pakistani context. The study was conducted in three phases. Phase I included forward translation, reconciliation, and back translation of the BSEI, conducted by expert psychologists and linguists. Phase II involved assessing cross-language validity with a sample of bilingual adults. Phase III was dedicated to establishing the scale’s factor structure and reliability using a sample of 750 participants. Confirmatory Factor Analysis (CFA) and reliability analysis were conducted to evaluate the psychometric strength of the Urdu version. High correlations (.73 to .93) between the English and Urdu versions confirmed empirical equivalence. CFA results demonstrated acceptable model fit (GFI = .928, AGFI = .911, RMSEA = .055), though some indices (CFI = .802, TLI = .778) were marginal. Internal consistency (Cronbach's alpha = .82) and test-retest reliability (r = .85) were high. The Urdu version of BSEI is a valid and reliable measure of self-esteem for Urdu-speaking populations in Pakistan.